2016
DOI: 10.1111/are.13054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cortisol and triiodothyronine bath treatments on the digestive enzyme profile and growth ofCatla catlalarvae during ontogenic development

Abstract: Digestive enzyme profile is a good indicator of the nutritional and health status of the fish. The present investigation aims to evaluate the effect of exogenous bath treatment of hormones, cortisol and triiodothyronine, on the digestive enzyme activities and growth of carp Catla catla (Ham.) during ontogenic development. Catla larvae (4 days old) were given bath treatment with cortisol (hydrocortisone, 0.2 mg L À1 ), 3,5,3 0 -triiodothyronine (T3, 2.5 mg L À1 ) and a combination of cortisol and T3 for 30 min.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Finally, we tested if GC and TH hormones had interactions, 4 of 42 such as synergistic effects, affecting offspring mitochondrial function, growth and survival (Brown et al, 2014). For instance, it has been shown that postnatal supplementation with THs and GC has synergistic effects on growth (Khangembam et al, 2017). Yet, directional predictions about the effects of prenatal hormones are very difficult to make considering 1. the likely environmental-dependence of their cost-benefit balance, 2. the existence of non-linear dose-responses and 3. the fact that embryos are not passive receivers of maternal hormones but can manipulate such signals (Groothuis et al, 2019).…”
Section: Of 42mentioning
confidence: 99%
“…Finally, we tested if GC and TH hormones had interactions, 4 of 42 such as synergistic effects, affecting offspring mitochondrial function, growth and survival (Brown et al, 2014). For instance, it has been shown that postnatal supplementation with THs and GC has synergistic effects on growth (Khangembam et al, 2017). Yet, directional predictions about the effects of prenatal hormones are very difficult to make considering 1. the likely environmental-dependence of their cost-benefit balance, 2. the existence of non-linear dose-responses and 3. the fact that embryos are not passive receivers of maternal hormones but can manipulate such signals (Groothuis et al, 2019).…”
Section: Of 42mentioning
confidence: 99%
“…The higher crypt depth of the duodenum and jejunum in parental pigeons during the early chick-rearing period was found in the present study; therefore, an increased proportion of immature cells in the epithelium could be a reason for the lower specific activities of at least some enzymes ( de Both and Plaisier, 1974 , Willing and Kessel, 2009 ). Intestinal adaptation in different breeding stages was speculated to be regulated by specific hormones ( Baksheev and Fuller, 2000 ), such as glucocorticoids, cortisol, and triiodothyronine, which were already found to affect the digestive enzymes in animals ( Chapple et al., 1989 ; Khangembam et al., 2017 ). Our previous study showed that the prolactin concentration rapidly reached the peak value in both sexes on the first day of chick-rearing, but the estradiol concentration in female pigeons remained low until the late chick-rearing period ( Xie et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%